2002
DOI: 10.1557/proc-715-a26.5
|View full text |Cite
|
Sign up to set email alerts
|

High Rate Deposition of Microcrystalline Silicon Solar Cells Using 13.56 MHz PECVD – Prerequisites and Limiting Factors

Abstract: Microcrystalline silicon (μìc-Si:H) solar cells were prepared in a wide range of deposition parameters using high pressure 13.56 MHz plasma-enhanced chemical vapor deposition (PECVD). Focus was on the influence of deposition pressure, electrode distance and the application of a pulsed plasma on high rate deposition of solar cells. At electrode distances between 5 and 20 mm solar cells with efficiencies >8 % were prepared. A medium electrode distance of 10 mm yielded best device performance. Pulsed plasma de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
33
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 11 publications
3
33
0
Order By: Relevance
“…Like in previous reports on various deposition conditions or methods for c-Si:H solar cell material, 12,18,19 it was found that also with PECVD under VHF-hphP conditions optimum solar cells are prepared close to the transition from a highly crystalline to an amorphous growth with, as we shall call it, an optimum phase mixture ͑OPM͒ of I C RS 488 Х 60%. Most importantly, it was found that a high solar cell performance is still available at considerably high deposition rates.…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…Like in previous reports on various deposition conditions or methods for c-Si:H solar cell material, 12,18,19 it was found that also with PECVD under VHF-hphP conditions optimum solar cells are prepared close to the transition from a highly crystalline to an amorphous growth with, as we shall call it, an optimum phase mixture ͑OPM͒ of I C RS 488 Х 60%. Most importantly, it was found that a high solar cell performance is still available at considerably high deposition rates.…”
Section: Discussionsupporting
confidence: 67%
“…Such OPM material, which results in the highest solar cell efficiencies, was found close to the transition from highly crystalline to amorphous growth in several earlier studies with different deposition methods. 12,18,19 Here we show that a similar behavior is found for the VHF-PECVD under high working pressure and high power ͑hphP͒ conditions. The shift of the OPM growth regime upon the variation of the deposition conditions, such as power and gas flow, and the behavior of the growth rates shall be discussed with an illustrative scheme for c-Si:H growth, with the ratio of H over SiH x ͑x =1, 2, or 3, same hereinafter͒ radicals as the key parameter.…”
Section: Introductionsupporting
confidence: 77%
See 1 more Smart Citation
“…An effect that is generally observed [4,21] when one increases the silane concentration used for the deposition of the i-layer is a steady increase in the V oc ; followed by an abrupt change close to the mc-Si:H/a-Si:H transition [7]. The evolution of V oc with silane concentration for the nip series deposited on sputtered ZnO is given in Fig.…”
Section: Link With Electrical Solar Cell Performancesmentioning
confidence: 80%
“…On the other hand, it is well known that the material microstructure depends as well on silane concentration [1,5]. At present, the best electrical performances are achieved for mc-Si:H solar cells with their i-layer deposited near the transition [6,7]. Under these conditions, the microstructure of mc-Si:H varies in the course of the growth process of the i-layer: a fully amorphous incubation layer is generally observed for the initial growth region (i.e.…”
Section: Introductionmentioning
confidence: 99%